2014
DOI: 10.1186/1479-5868-11-54
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional associations between the screen-time of parents and young children: differences by parent and child gender and day of the week

Abstract: BackgroundGreater time spent screen-viewing (SV) has been linked to adverse health outcomes. The aim of this study was to examine whether parental SV time is associated with child SV time on week and weekend days.MethodsCross-sectional survey of 1078 children aged 5–6 and at least 1 parent. Child and parent SV was reported for weekday and weekend days. Logistic regression examined whether parental SV time was associated with child SV time, with separate analyses for mothers and fathers and interaction terms fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
123
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(142 citation statements)
references
References 27 publications
16
123
0
3
Order By: Relevance
“…Furthermore, our results are consistent with the findings of other studies (Jago et al, 2014;Kourlaba et al, 2009;Mendoza et al, 2007), which found that one of the most important behavioural determinants of young children's ST is the ST of their parents (Jago et al, 2014). However, our study complements this finding by observing different patterns for weekdays vs. weekends.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Furthermore, our results are consistent with the findings of other studies (Jago et al, 2014;Kourlaba et al, 2009;Mendoza et al, 2007), which found that one of the most important behavioural determinants of young children's ST is the ST of their parents (Jago et al, 2014). However, our study complements this finding by observing different patterns for weekdays vs. weekends.…”
Section: Discussionsupporting
confidence: 81%
“…In accordance with other studies of parental proxy-reported sedentary behaviour (Cardon et al, 2016;De Craemer, Lateva, et al, 2015;Jago et al, 2014;Kourlaba, Kondaki, Liarigkovinos, & Manios, 2009), the Czech preschool children and their parents, regardless of gender and body weight level, showed higher ST at weekends than on weekdays.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Higher parental TV viewing has been associated with increased risk for high levels of TV viewing for both boys and girls (Jago et al, 2010;Jago et al, 2014;Jago et al, 2013). Further, children who live in homes with increased access to media equipment have been shown to engage in greater TV viewing (Jago et al, 2013).…”
Section: Home Settingsmentioning
confidence: 99%
“…Unfortunately, some parents can be distracted by media and miss important opportunities for emotional connections that are known to improve child health. 53,54 One research study found that when a parent turned his or her attention to a mobile device while with a young child, the parent was less likely to talk with the child. 55 Parental engagement is critical in the development of children's emotional and social development, and these distractions may have short-and long-term negative effects.…”
Section: Parent Media Use and Child Healthmentioning
confidence: 99%